Abstracts Collection from the 2024 International Forum of the SEA-EU Observatory of Migration and Human Rights: The EU Pact on Migration and Asylum: Navigating the Crossroads of Governance, Human Rights, and Europe’s Borders - Observatory of Migration; Human Rights, SEA-EU; Jiménez García-Carriazo, Ángeles (PEACE & SECURITY-PAIX ET SÉCURITÉ INTERNATIONALES (EuroMediterranean Journal of International Law and International Relations), 2026)
In a time of growing global instability and increasingly complex migration dynamics, the 2024 International Forum of the SEA-EU Observatory of Migration and Human Rights, held in Algeciras (Cadiz) on 7th and 8th November 2024, served as a timely and urgent space for critical reflection. Centered on the theme “The EU Pact on Migration and Asylum: New Challenges for Migration Management and Human Rights at Europe’s Borders”, the forum brought together scholars, experts, and practitioners from the SEA-EU Alliance to address the evolving landscape of European migration governance and its human rights implications. The event focused on the EU Pact on Migration and Asylum, an initiative proposed in 2020 and advanced through legislative developments in subsequent years, as a lens through which to explore the challenges, contradictions, and ambitions of European migration policy. Through a rich and diverse programme of lectures, round tables, and academic communications, the forum encouraged rigorous examination of the Pact’s legal, ethical, political, and social dimensions.